Design considerations for parallel chord one-way long-span steel trusses - Schmits, Brice (Kansas State University, 2009)
This report is designed to be a valuable tool for any engineer who has had proper instruction in load paths and knowledge of structural steel design but is not familiar with truss systems and has never designed a long-span steel truss. In other words, for someone who knows the math and concepts but not the means, methods, and practical limitations of truss design. By applying their knowledge of engineering concepts and some good judgment with the information in this report they will be able to design an efficient truss. The type of truss considered has a span of 100’ to 200’, is parallel chord, one-way, simply spanned, and constructed of steel. The trusses are evaluated for typically gravity loading and analyzed in two dimensions. Aspects from analysis, layout, fabrication, erection, and transportation are investigated to find ideal methods of design and practical limitations for this type of truss. Once this information is learned it can be to be applied to an individual truss on an individual basis. Engineers need to realize that even though a truss could be designed with the most efficient use of steel it may not be the most economic solution. One must also realize too many variables are present to form rules or equations to always yield the perfect truss. Only by coupling proper design and analysis with knowledge of fabrication and erection will one be able to design an efficient truss.
Keywords: truss; steel; long; span; Engineering, Civil (0543)